From synaptic plasticity to spatial maps and sequence learning. Issue 6 (June 2015) - Mehta, Mayank R.
Abstract: The entorhinal–hippocampal circuit is crucial for several forms of learning and memory, especially sequence learning, including spatial navigation. The challenge is to understand the underlying mechanisms. Pioneering discoveries of spatial selectivity in this circuit, i.e. place cells and grid cells, provided a major step forward in tackling this challenge. Considerable research has also shown that sequence learning relies on synaptic plasticity, especially the Hebbian or the NMDAR‐dependent synaptic plasticity. This raises several questions: Are spatial maps plastic? If so, what is the contribution of Hebbian plasticity to spatial map plasticity? How does the spatial map plasticity contribute to sequence learning? A combination of computational and experimental studies has shown that NMDAR‐mediated plasticity and theta rhythm can have specific effects on the formation and experiential modification of spatial maps to facilitate predictive coding. Advances in transgenic techniques have provided further support for these mechanisms. Although many exciting challenges remain, these findings have brought us closer to solving the puzzle of how the hippocampal system contributes to spatial memory, and point to a way forward. © 2015 Wiley Periodicals, Inc.